Inhibiting Protein Kinase D Promotes Airway Epithelial Barrier Integrity in Mouse Models of Influenza A Virus Infection - Veazey, Janelle M.; Eliseeva, Sophia I; Hillman, Sara E.; Stiles, Kristie; Smyth, Timothy R.; Morrissey, Charlotte E.; Tillotson, Erika J.; Topham, Dave J.; Chapman, Timothy J.; Georas, Steve N. (Frontiers in Immunology, 2020)
Rationale: Protein kinase D (PKD) is a serine/threonine kinase family that is involved in a wide array of signaling pathways. Although PKD has been implicated in immune responses, relatively little is known about the function of PKD in the lung or during viral infections. Objectives: We investigated the hypothesis that PKD is involved in multiple aspects of host response to viral infection. Methods: The selective PKD inhibitor CRT0010166 was administered to C57BL/6 mice prior to and during challenge with either inhaled double-stranded RNA or Influenza A Virus. PKD signaling pathways were investigated in human bronchial epithelial cells treated with CRT0010166, double-stranded RNA, and/or infected with Influenza A Virus. Measurements: Total protein and albumin accumulation in the bronchoalveolar fluid was used to asses inside/out leak. Clearance of inhaled FITC-dextran out of the airspace was used to assess outside/in leak. Cytokines and neutrophils in bronchoalveolar lavage were assayed with ELISAs and cytospins respectively. Viral RNA level was assessed with RT-PCR and protein level assessed by ELISA. Main Results: PKD inhibition prevented airway barrier dysfunction and pro-inflammatory cytokine release. Epithelial cells express PKD3, and PKD3 siRNA knock-down inhibited polyI:C induced cytokine production. Lung epithelial-specific deletion of PKD3 (CC10-Cre x PKD3-floxed mice) partially attenuated polyI:C-induced barrier disruption in vivo. Mechanistically, we found that PKD promoted cytokine mRNA transcription, not secretion, likely through activating the transcription factor Sp1. Finally, prophylactic CRT treatment of mice promoted barrier integrity during influenza virus infection and reduced viral burden. Conclusions: Inhibiting PKD promotes barrier integrity, limit pathogenic cytokine levels, and restrict Influenza A Virus infection. Therefore, PKD is an attractive target for novel antiviral therapeutics.